Are entrepreneurs becoming more risk averse?. Issue 1 (14th January 2019) - Oliver, John J.; Velji, Newton
Abstract : Purpose: This paper aims to discuss the emerging theme of risk aversion in entrepreneurs following high levels of industry consolidation. Design/methodology/approach: This paper is a viewpoint on the authors' opinion and interpretation of industry consolidation. Findings: The UK Independent TV Production Industry has experienced a remarkable degree of consolidation with corporate acquisitions and mergers changing the size, shape and revenue distribution among firms in the industry. In addition, entrepreneurs appear to be more risk averse in terms of entering the industry. Practical implications: If the trend in entrepreneurs in the UK TV Production Industry being more risk averse continues, then the number of new startup firms will fall and that could put the future of the industry at jeopardy. Originality/value: This paper presents an interesting observation on the impact of consolidation of the UK Independent TV Production Industry, in so far as, entrepreneurs appear to be becoming more risk averse.